Legal Institutions in Resolving Divorce Cases in Aceh - Muhazir, Muhazir; Azwir, Azwir; Zubir, Zubir (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to examine the legal institutions involved in divorce settlement in Langsa City. Apart from that, this study also analyzes the influence of each institution on the solution to the divorce problem in Aceh. Empirical legal studies are carried out using social and legislative frameworks. A statute approach is used to examine the legal elements in the process of resolving divorce cases, while a sociological approach is used to examine the social components of divorce practice. This study found that the Gampong traditional institution has more influence than the Sharia Court in resolving divorce cases. Even though state law does not allow divorce outside of court, the community believes that the Gampong traditional institution can resolve divorce cases more quickly, cheaply, easily, and with ease. more sacred. This differs from divorce in religious courts, which usually takes time, and filing takes time. Divorce through religious courts is used by the community when the parties want to legalize their new marriage. This study concludes that the influence of traditional institutions is very strong for the people of Langsa City because traditional institutions are able to resolve divorce problems easily and quickly. This study contributes to a distinct viewpoint on divorce by demonstrating that, in addition to state institutions, traditional institutions play an essential role in resolving divorce cases. Without disobeying state laws, the government need to respect traditional institutions' rulings in divorce situations. This implies that a conventional institution's decision may serve as a basis for the law in divorce situations. Aside from that, a court divorce still carries a bad reputation in society because of the length, difficulty of the procedure, and perceived difficulty of the operations.